The neurocognitive basis of Chinese idiomatic constructions and processing differences between native speakers and L2 learners of Mandarin - Liu, Te-Hsin; Lai, Chia-Ho; Chou, Tai-Li (Frontiers in Psychology, 2023)
Classic linguistic analyses assume that syntax is the center of linguistic system. Under this assumption, a finite set of rules can produce an infinite number of sentences. By contrast, construction grammar posits that grammar emerges from language use. Chinese quadrisyllabic idiomatic expressions (QIEs) offer a testing ground for this theoretical construct owing to their high productivity. To understand the cognitive processing of structure and meaning during reading comprehension, we used a semantic judgment task to measure behavioral performance and brain activation (functional magnetic resonance imaging). Participants were nineteen Mandarin native speakers and nineteen L2 learners of intermediate and advanced levels of Mandarin. In the task, participants were instructed to indicate whether the interpretation of a QIE was correct. Our behavioral results showed that L2 learners processed high frequency QIEs faster than low frequency ones. By contrast, low frequency QIEs were processed faster than high frequency ones by native speakers. This phenomenon may be attributed to semantic satiation which impedes the interpretation of high frequency QIEs. To unravel the puzzle, a further functional magnetic resonance imaging experiment on native speakers was conducted. The results revealed that the comparison of high-frequency and low-frequency QIEs promoted significant anterior cingulate activation. Also, the comparison of idiomatic and pseudo-idiomatic constructions exhibited significant activation in the bilateral temporal poles, a region that computes semantics rather than syntactic structure. This result indicated that, for native speakers, processing Chinese idiomatic constructions is a conceptually driven process.